Early nutrition approach in critically ill COVID-19 patients - Niken Puruhita (World Nutrition Journal, 2020)
This presentation is aimed to describe several guidelines available indicating nutritional therapy in critically ill COVID-19 patients. Data from our ICU in dr. Kariadi General Hospital will be presented.